Colchicine derivatives with potent anticancer activity and reduced P-glycoprotein induction liability12. Issue 20 (21st April 2015) - Singh, Baljinder; Kumar, Ashok; Joshi, Prashant; Guru, Santosh K.; Kumar, Suresh; Wani, Zahoor A.; Mahajan, Girish; Hussain, Aashiq; Qazi, Asif Khurshid; Kumar, Ajay; Bharate, Sonali S.; Gupta, Bishan D.; et al.
Abstract : Colchicine derivatives with reduced P-gp induction liability have been identified. Abstract : Colchicine (1 ), a nature-derived microtubule polymerization inhibitor, develops multi-drug resistance in tumor cells due to its P-gp substrate and induction activity, which in turn leads to its rapid efflux from tumor cells. This auto-induction of the efflux of colchicine remains a major challenge to medicinal chemists. Based on structure-based molecular modeling, a series of new colchicine derivatives were designed and synthesized with a potential for reduced P-gp induction liability. Screening of the prepared derivatives for P-gp induction activity revealed that a number of derivatives possess remarkably lower P-gp-induction activity (>90% intracellular accumulation of rhodamine 123 in LS-180 cells) compared to the parent natural product colchicine (62% Rh123 accumulation in LS-180 cells). The reduced P-gp-induction activity of new derivatives may be due to their reduced ability to interact and change the conformation of P-gp. The synthesized derivatives were then screened for antiproliferative activity against two colon cancer cell lines including HCT-116 and Colo-205. The derivative4o showed potent cytotoxicity in HCT-116 cells with IC50 of 0.04 μM with significantly reduced P-gp induction liability. Compound4o also inhibited microtubule assembly and induced expression of pro-apoptotic protein p21. In an Ehrlich solid tumor mice model, compound4o showed 38% TGI with no mortality at 2 mg kg −1 dose (oral). Compound4o, with potent in vitro and in vivo anticancer activity, significantly reduced P-gp induction activity and its excellent physicochemical and pharmacokinetic properties open up new opportunities for the colchicine scaffold.